Public Debt and Economic Growth in Africa in the Pre-Covid Era: The Role of Control of Corruption - Abotsi, Anselm Komla; Ampah, Isaac Kwesi (International Journal of Economics and Financial Issues, 2024)
There is evidence of recent rising public debts and low economic growth in Africa which is being attributed to the COVID-19 pandemic and the geopolitical tensions from the Russia-Ukraine war. With the evidence of also recent high corruption amidst low investments in Africa, it is thought-provoking to find empirically how public debt impact on economic growth per capita among African countries even before the COVID-19 pandemic and the geopolitical tensions from the Russia-Ukraine war with the mediation of control of corruption. The study used secondary data from the World Development Indicators, World Economic Outlook, and Worldwide Governance Indicators. The annual data spans from 1996 to 2019 for 45 countries. The study deployed a dynamic panel data estimation technique and controlled for other variables. The findings show a negative impact of gross debt percentage of GDP on economic growth but a positive interactive effect of excessive accumulation of gross public debt and the control of corruption on economic growth per capita among countries in Africa before the outbreak of the COVID-19 pandemic. In this COVID era of high public debt, governments can reduce their indebtedness by financing appropriate infrastructure while controlling corruption to increase the economic growth in their countries.